Peptides Selected for Binding to a Virulent Strain of Haemophilus influenzae by Phage Display Are Bactericidal - Bishop-Hurley, Sharon L. (American Society for Microbiology, 2005)
Nontypeable Haemophilus influenzae (NTHi) is an obligate parasite of the oropharynx of humans, in whom it commonly causes mucosal infections such as otitis media, sinusitis, and bronchitis. We used a subtractive phage display approach to affinity select for peptides binding to the cell surface of a novel invasive NTHi strain R2866 (also called Int1). Over half of the selected phage peptides tested were bactericidal toward R2866 in a dose-dependent manner. Five of the clones encoded the same peptide sequence (KQRTSIRATEGCLPS; clone hi3/17), while the remaining four clones encoded unique peptides. All of the bactericidal phage peptides but one were cationic and had similar physical-chemical properties. Clone hi3/17 possessed a similar level of activity toward a panel of clinical NTHi isolates and H. influenzae type b strains but lacked bactericidal activity toward gram-positive (Enterococcus faecalis, Staphylococcus aureus) and gram-negative (Proteus mirabilis, Pseudomonas aeruginosa, and Salmonella enterica) bacteria. These data indicate that peptides binding to bacterial surface structures isolated by phage display may prove of value in developing new antibiotics.